Tibial Eminence Avulsion Fracture in Pediatric Patients Reinserted with Arthroscopy and Pull-Out Suture Technique: Clinical and Functional Outcomes in a Long-Term Follow Up with Return to Sport - Franziska M. Kocher; Ludovic Galofaro; Joseph M. Schwab; Ines Raabe; Moritz Tannast; Daniel Petek (Children)
Background/Objective: Tibial eminence avulsion fracture (TEAF) is a traumatic injury of the anterior cruciate ligament that occurs in children with an immature skeletal system. It has an incidence of 3 per 100,000 children, with an increasing prevalence over time. The objective of this study was to evaluate the long-term clinical and subjective outcomes of displaced TEAF requiring surgical intervention and to assess the return to sport. Methods: A retrospective cohort study was conducted, identifying all patients who underwent arthroscopic-assisted TEAF refixation at HFR-Fribourg between 2012 and 2020, performed by a single surgeon. A total of fifteen patients were included for descriptive analysis, while twelve patients underwent clinical assessment of knee joint stability and functional outcomes using patient-reported outcome measures (PROMs): Pedi-IKDC, Lysholm, Tegner, and Marx. Results: Of the fifteen patients, fourteen had type III and one had type II TEAF according to the McKeever classification. The mean age at the time of injury was 11.5 years, and the average time between surgery and long-term follow-up was 5.1 years (range: 0.9–8.9 years). For the primary outcomes of the operated knee, no significant differences were observed in muscle mass or range of motion between the operated and non-operated limbs (p > 0.05). Anterior knee stability, as assessed by the Lachman test and Rolimeter, showed no significant difference between the operated and non-operated knee (p > 0.05). Regarding secondary outcomes, the Pedi-IKDC and Lysholm scores were 98 out of 100, the Tegner score was 5.5 out of 10, and the Marx score was 14.5 out of 20 at the final follow-up. There were no significant differences in the number of hours per week or frequency of sport activity (mean three times per week) before and after surgery. Conclusions: The surgical treatment for displaced TEAF, specifically the pull-out suture technique with arthroscopic assistance, demonstrates excellent clinical and functional outcomes, with high recovery rates and restored knee stability. This technique allows patients to return to sports without significant impairment. Although no comparative analysis was performed, these findings provide a foundation for future studies to further validate and compare the effectiveness of this surgical approach.